Methodology for evaluating the social intelligence of a coach - Smoldovskaya, I. O.; Krasavtseva, E. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was the development and psychometric analysis of the "Social intelligence of a coach" methodology.